Youth and Politics in Turkey in the Context of Education and Cultural Policies - Koroglu, Ahmet (CenRaPS Journal of Social Sciences, 2020)
The educational and cultural policies in Turkey are among the important issues impacting Turkish society and inherited from the Ottoman period. These issues show themselves in Turkey’s conception of civilization and perception of the world in particular. Therefore, Turkey’s educational and cultural policies are the main factor in detecting and specifying this conception and perception. On the point where even the conceptual definition of education and culture is exceedingly difficult, these concepts turn into a policy at the practical level, which is a problem in itself. The Republic of Turkey has deeply experienced this problem, and the steps taken on this topic have brought together many new and different problems. This article will primarily address the relationship of education and culture with youth as well as examine the process of how they transform into a policy. Later the practical developments of these phenomena will be examined with a certain historical process. At that point, the educational and cultural policies dating from the foundation of the Republic to the present will be discussed both through the breaking points as well as through the governmental and political-party programs. Last but not least, the article will briefly examine the objectives of these policies and what effect it has had on the 21st century Turkish youth.